Gestión de Sistemas de Informacion- AF188- 202202 - Burga Durango, Daniel Wilfredo (2022)
The pervasiveness of computer-based information technology (IT) in nearly all aspects of business means every individual in business needs to understand enough about IT to incorporate technology effectively into their enterprise. The content from this course will introduce you to many concepts of information technology in business and organizations. Information systems are firmly rooted in an organizational context, so this is not merely a "technical" or "computer" course; this is a business course which involves the understanding of concepts and application of technical skills. Information systems are increasingly becoming more strategic and intertwined with the social systems in organizations, so this course will have a "strategic business" and "socio-technical" rather than a purely techno-centric perspective. The course syllabus, lecture material, assignments, etc. for this course are available on the D2L course website.